Student Support Services Towards Institutional Change and Development - Josephine Diana S Campos; Jofrey R Campos (Education Policy and Development, 2023)
Assurance of quality and assessment of the current state of services provided by government-funded colleges and universities are constantly dominating the agenda in most countries. Developing countries in the Asia Pacific, such as the Philippines, are concerned with continuously improving their academic standards while pursuing greater access and opportunity. Quality arrangements are now being sought to balance quantity, quality, and public accountability as it moves toward mass higher education with a greater diversity of students and modes combined with tightened or limited resources. As a result, SUCs (State Universities and Colleges) and LUCs (Local Universities and Colleges) are expected to constantly respond to changes in the higher education environment to address their students' diverse learning and support needs. Under such circumstances, this study is relevant. The main objective of this research is to cover the student assistance services offered by SUCs and LUCs, given that higher education institutions are focusing on meeting the standards assigned by recognized accreditation agencies on a standard-by-standard basis. Since HEIs (Higher Education Institutions) place a high value on quality assurance, and institutional and program accreditation leveling for global recognition, this study determined the current state of SSP as perceived by student respondents. This research is limited to a particular degree program (Bachelor of Science in Business Administration) from the following government-funded HEIs: University of Makati (UMak), Nueva Ecija University of Science and Technology (NEUST), Bulacan Agricultural State College (BASC), Eulogio "Amang" Rodriguez Institute of Science and Technology (EARIST), and Bulacan State University (BulSU).